FAKTOR-FAKTOR YANG MEMPENGARUHI LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Vinola Herawaty (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2020)
The objective of this study is to analyze the influence of leverage, profitability,, industry type and foreign ownership to Corporate Social Responsibility Disclosure. The method of this  research is a hypothesis testing which explaining the phenomenon of the relationship between variables. Data used in this study come from annual reports and financial reports of manufacturing companies listed on the Indonesia Stock Exchange in period 2016-2018. Analysis of the hypothesis used in this study using linear regression. The difference between this research and previous research is adding foreign ownership variable because foreign ownership are parties that are considered to be concerned about the wide disclosure of corporate social responsibility. This study shown that the results of leverage, industry type and foreign ownership have positive influences to Corporate Social Responsibility Disclosure, while profitability does not has a significant effect to Corporate Social Responsibility Disclosure